As contribuições do PIBID de Língua Portuguesa para a formação contínua: entrelaçando competências e saberes docentes - Zimmer, Denise Raquel (2016)
This research sought to reflect and analyze the possible contributions of the Institutional Scholarship Program to Encourage Teaching known as PIBID to the process of continuous formation of four supervisors teachers of the Portuguese subproject of PIBID-Unioeste developed from 2011 to 2014. From studies realized and as it is a recent program, little investigated; emerged us some questions that stood out as a guide for our research: How the activities and actions developed by supervisors teachers in the PIBID/Unioeste of Portuguese Language have contributed to their continuing education? What skills and knowledge for teaching were discussed during the PIBID that can collaborate with the teaching practice of these Basic Education teachers? In order to find answers to these questions, we draw as a general objective to analyze the PIBID contributions to continuing education and teaching practice of the supervisors teachers of the subproject of Portuguese language, with specific objectives outlined: To identify the activities and actions carried out by supervisors teachers within the program; to check which skills and knowledge for teaching were addressed during the PIBID; to point what the supervisors teachers report about possible reflections and changes in their teaching practice from their participation in PIBID. To achieve the goals, we sustain our research on theoretical assumptions about the continuing education Nóvoa (1992; 1997; 2000; 2002), Candau (1997; 1999), Pimenta (1999) Libâneo, Oliveira and Toschi (2003), Costa-Hübes (2008); we also deal in our theoretical studies about the teaching knowledge of TARDIF (2012), Freire (2009) among others; and the abilities related to the act of teaching - Perrenoud (2000), Libâneo (1991), Pimenta (2005), among others. The data generation was collected through interviews with semi-structured, individually performed and recorded audio. It is, therefore, a search guided by the Applied Linguistics, the interpretive qualitative type. The research reveals interesting facts about the PIBID contributions to the training of supervisors teachers of the subproject of Portuguese, with respect to reflection and change in teaching practice through closer ties with the university, broadening and deepening the knowledge and skills of the act of teaching